2021
DOI: 10.1016/j.celrep.2021.109782
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive Notch-Dll4 and Klf2-Wnt9 signaling pathways intersect in guiding valvulogenesis in zebrafish

Abstract: Highlights d Atrioventricular valvulogenesis in zebrafish is regulated by Notch and Klf2 pathways d Notch-mediated lateral inhibition singles out Delta-like-4positive endocardial cells d These cells ingress into the cardiac jelly in response to Erk5-Klf2-Wnt9a signaling d Frizzled9b makes presumptive ingressing endocardial cells competent to respond to Wnt9a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
4
20
0
Order By: Relevance
“…We demonstrated that Wnt/β-catenin signaling reporter line exhibited disrupted expression pattern, while Notch-activated cells in the corresponding reporter line didn’t show any effect. The different activities of Notch and Wnt/β-catenin observed in cfdp1 mutant hearts indicate the composition of two different cell subsets, in accordance to previously reported Notch-activated luminal AV cells and Wnt/β-catenin-activated abluminal AV cells during valve formation 39,69 . Moreover, it has been shown that although Notch and Wnt signaling intersect in order to promote the TCF-positive endocardial cells ingression into cardiac jelly during valvulogenesis, inhibition of Erk5-Klf2 pathway impairs canonical Wnt signaling without affecting Notch nor Dll4 activation in atrioventricular endocardial cells, confirming that these pathways are regulated independently 69 .…”
Section: Discussionsupporting
confidence: 90%
“…We demonstrated that Wnt/β-catenin signaling reporter line exhibited disrupted expression pattern, while Notch-activated cells in the corresponding reporter line didn’t show any effect. The different activities of Notch and Wnt/β-catenin observed in cfdp1 mutant hearts indicate the composition of two different cell subsets, in accordance to previously reported Notch-activated luminal AV cells and Wnt/β-catenin-activated abluminal AV cells during valve formation 39,69 . Moreover, it has been shown that although Notch and Wnt signaling intersect in order to promote the TCF-positive endocardial cells ingression into cardiac jelly during valvulogenesis, inhibition of Erk5-Klf2 pathway impairs canonical Wnt signaling without affecting Notch nor Dll4 activation in atrioventricular endocardial cells, confirming that these pathways are regulated independently 69 .…”
Section: Discussionsupporting
confidence: 90%
“…A second cleavage by γ-secretase then releases the intracellular domain, NICD, which forms a complex with a DNA-binding transcription factor and a co-activator to regulate transcription of target genes. In many developmental processes, Notch activation occurs contemporaneously with morphological changes which could modulate pathway activity so that signaling and tissue rearrangements are coordinated ( Paolini et al, 2021 ; Han et al, 2021 ; Engel-Pizcueta and Pujades, 2021 ; Lloyd-Lewis et al, 2019 ). For example, cell shape or tension changes in the neighboring cells could impact on the forces exerted on the receptor to alter the amount of cleavage ( Shaya et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Klf2a has been shown to act in parallel with Notch to inhibit Flt4, a protein that is thought to be expressed in abluminal cells of zebrafish superior AV valves and strongly expressed in cells undergoing EndoMT in mouse AV valves [ 55 ]. Meanwhile, mechanosensitive Notch-Delta-like-4 and Erk5-Klf2-Wnt9a signaling pathways act together to regulate early zebrafish superior AV valve formation [ 62 ]. Specifically, Notch-mediated lateral inhibition between endocardial cells is thought to single out Delta-like-4-positive endocardial cells, which acquire competence to respond to Wnt9a.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Notch-mediated lateral inhibition between endocardial cells is thought to single out Delta-like-4-positive endocardial cells, which acquire competence to respond to Wnt9a. Concurrently, Wnt9a is produced downstream of Klf2, leading to the ingression of Delta-like-4-positive endocardial cells [ 62 ]. Finally, Klf2-Wnt/β-catenin signaling is thought to limit mesenchymal cell proliferation in mouse valves during remodeling stages [ 17 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation